2018
DOI: 10.1139/cjpp-2017-0578
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic and cytoprotective signaling cascades mediate the mitigative effect of erythropoietin on acute radiation syndrome

Abstract: The present investigation aimed to evaluate the radiomitigative efficacy of the recombinant human erythropoietin (EPO) against acute radiation syndrome (ARS) in a rat model. Rats were irradiated with a single sublethal dose of γ-radiation (7 Gy; total body irradiation; TBI) on the 1st day of experimental course, then received EPO (5000 IU/kg; i.p.) 24 h after irradiation, and rats were observed for 30 days of survival analysis. Administration of EPO improved 30-day survival, alleviated TBI-induced myelosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
2
4
0
Order By: Relevance
“…These findings were supported by the physiological liver and kidney function measurements and histopathological investigation, whereas the changes in the architecture and functions of these tissues that responded to the oxidative damages and inflammation were observed. These data are in agreement with the previous findings shown in several studies by El Bakary et al, 10 Moustafa and Thabet, 26 Galal et al, 27 and Qin et al 6…”
Section: Discussionsupporting
confidence: 94%
“…These findings were supported by the physiological liver and kidney function measurements and histopathological investigation, whereas the changes in the architecture and functions of these tissues that responded to the oxidative damages and inflammation were observed. These data are in agreement with the previous findings shown in several studies by El Bakary et al, 10 Moustafa and Thabet, 26 Galal et al, 27 and Qin et al 6…”
Section: Discussionsupporting
confidence: 94%
“…Before sacrificed, final body mass of the mice was weighed. Immediately after the mice were sacrificed, the liver tissues were collected, weighed and liver mass index was calculated according to the following equation (Galal et al, 2018 ): …”
Section: Methodsmentioning
confidence: 99%
“…[26][27] Several studies have reported that the detrimental effects evolved after irradiation were connected to the status of oxidative stress and imbalance of oxidation/ reduction (redox) system. [28][29][30] It seemed that, the ROS generated after γ-radiation exposure attacks antioxidant molecules and resulted in consumption of liver and spleen contents of GSH in ROS neutralization process. In addition, the plenty of ROS interact with the lipid molecules that organized in the cellular structures of liver and spleen causes increasing in tissue contents of MDA which leads in turn to loss of cellular and tissues redox tone and finally the development of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the exposure to γ-radiation induced a status of imbalance between proinflammatory (such as NF-κB and IL-6) and antiinflammatory (IL-10 and α-7nAchR) secretion. [29][30] Also, gamma irradiation endorses the secretion of inflammatory cytokine IL-17 that applies in a variety of biological effects by binding to its receptors which broadly expressed on the surface of numerous cells and has imperative roles in encouraging inflammation. 36 On contrary, the administration of Ag according to the present protocol reveals significant ameliorations in the inflammatory responses of rat's groups exposed to γ-irradiation.…”
Section: Discussionmentioning
confidence: 99%